2012
DOI: 10.3324/haematol.2012.066100
|View full text |Cite
|
Sign up to set email alerts
|

Survival for older patients with acute myeloid leukemia: a population-based study

Abstract: The online version of this article has a Supplementary Appendix. BackgroundAcute myeloid leukemia is the second most common leukemia among United States adults with a median age of 69 years. We investigated recent clinical practices related to treatments and disease outcomes in older patients with acute myeloid leukemia in the United States. Design and MethodsIn this retrospective cohort study, we used Surveillance, Epidemiology, and End Results program data from 2000 through 2007 linked to Medicare enrollment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
302
2
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 377 publications
(335 citation statements)
references
References 40 publications
(46 reference statements)
21
302
2
10
Order By: Relevance
“…Despite this, many older individuals continue to be offered only low intensity or best supportive care due to concerns about treatment-related mortality and morbidity with intensive regimens. In recent years, the HMAs, decitabine or azacitidine, have emerged as an alternative induction strategy for older AML patients [41]. Prior studies have demonstrated that HMA therapy results in equivalent or potentially superior outcomes over low-dose cytarabine or best supportive care in older AML patients deemed unsuitable for intensive chemotherapy [34,42].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite this, many older individuals continue to be offered only low intensity or best supportive care due to concerns about treatment-related mortality and morbidity with intensive regimens. In recent years, the HMAs, decitabine or azacitidine, have emerged as an alternative induction strategy for older AML patients [41]. Prior studies have demonstrated that HMA therapy results in equivalent or potentially superior outcomes over low-dose cytarabine or best supportive care in older AML patients deemed unsuitable for intensive chemotherapy [34,42].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, older individuals with poor-risk karyotype, wild-type NPM-1 mutation, secondary AML, and lower initial WBC may preferentially benefit from Epi therapy. Although not approved in the United States, the expanded off-label use of decitabine as an alternative induction approach for older AML patients has the potential to markedly increase the numbers (and outcomes) of individuals receiving definitive as opposed to supportive care only for this disease [41,42]. Epidemiological data from 2001 to 2009 have recently demonstrated a significant improvement both in percentage of older AML patients receiving treatment and the OS of patients as compared with 1992-2000 [41,53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent analysis of US SEER data from 2000 to 2007 revealed that only 38.6% of 5480 elderly AML patients (median age 78 years, range 65-93) received active leukemia therapy within 3 months of diagnosis. 3 This suggests that we need to challenge the status quo in AML treatment. In fact, our SEER study ( Figure 2) and Swedish registry data demonstrated that patients who received leukemia treatment had better survival compared to those who did not.…”
Section: Introductionmentioning
confidence: 99%